Development of Gelatin-Sodium Alginate Microparticles for Oral Insulin Delivery - Chibuzor Amadi, Ben (2024)
Oral delivery of peptide drugs in the management of diabetes remained a major challenge among formulation scientists in the pharmaceutical industry. In this study, insulin-loaded microparticles for oral delivery were prepared with gelatin and sodium alginate and combined at different ratios using the double emulsion technique. The insulin-loaded microparticles (MPs) were evaluated for yield, and particle size, shape and thermal properties were determined. The in vitro release of insulin and blood glucose reduction after oral administration to diabetic rats were determined. The microparticles formed were spherical and pitted. The prepared insulin-loaded microparticles showed a lag phase before insulin release. The gelatin:sodium alginate (Na-Alg) ratio of 0:1 was the only formulation that released the most in vitro. The percentage blood glucose reduction for subcutaneously administered insulin was significantly greater than that for the formulation (p < 0.05). The reduction effect observed after orally administered insulin-loaded MPs in batch with Na-Alg-gelatin (1:1) was observed after 9 h. However, this effect was like the effect observed insubcutaneously insulin solution. There was gradual release with a sustain effect of lower blood glucose level for a period of 24 h. These results are indicative of its effectiveness as an alternative for the delivery of insulin.